TECNOLOGIA DIDÁTICA INSTRUCIONAL PARA ADOLESCENTES: PREVENÇÃO DE GRAVIDEZ E INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS - Hadad, Andressa Bertiel Willeke (2023)
Human sexuality interferes with the integral understanding of human beings, as well as healthy and sustainable development. Investing in instructional technologies to support the understanding of sexuality among adolescents constitutes a prospective strategy for reducing pregnancy and sexually transmitted infections among adolescentsGeneral objective: to build a board-type educational game for teenagers, addressing the prevention of pregnancy and Sexually Transmitted Infections. Specific objectives: to understand the scientific evidence regarding approaches to preventing pregnancy and Sexually Transmitted Infections in adolescence, through educational games; describe the journey of creating a board game for teenagers, addressing the prevention of pregnancy and Sexually Transmitted Infections. Methodology consisted of methodological research that is part of a larger project entitled “Reduction of Pregnancy and Sexually Transmitted Infections in adolescence through intersectoral health education strategies'', approved in the call DECIT/SCTIE/MS-CNPQ-FAPERGS 08/ 2020 – research program for the SUS: Shared management in health – PPSUS and received funding from the Rio Grande do Sul Research Support Foundation (FAPERGS). For the narrative review research, the Virtual Health Library-VHL was used with the descriptors: adolescents, Health education, Sexually Transmitted Infection and Didactic games, linked by the Boolean operator and. The development of the product occurred in seven stages: 1st preliminary study, 2nd development of the idea, 3rd creation of the game layout, 4th elaboration of the game with questions and answers about adolescent sexual and reproductive health, 5th presentation of the game, 6th criteria for operating the game with teenagers, and 7th rules of the game. The technical nature of the product, according to Qualis Technical Production of Capes - T1 100 points, game-type instructional teaching material. Results are presented through two manuscripts, the 1st entitled: prevention of pregnancy and STIs: didactic games as a means to raise awareness among adolescents, the 2nd entitled: didactic technology for health promotion: Board Game for teenagers “Discovery Trail”. The game has fifty houses divided into six topics: Peak of general knowledge; sea of human sciences; tower of non-conception; valley of exact sciences; Menstrual cycle forest and sexual guru's cave. Up to five groups of teenagers can participate. Conclusion: The prevention of pregnancy and STIs must be discussed in the classroom, in a transversal way, directing healthy discussions with teenagers, and games can satisfactorily support these actions. Product and its applicability: The educational board game for teenagers will impact prevention of pregnancy and Sexually Transmitted Infections in adolescence and will contribute to the healthy and sustainable development of the country. The product can be replicated in different regions of the country.